Retributivism and The Objective Attitude - Jeppsson, Sofia (Diametros, 2024)
It has been argued that a retributivist criminal justice system treats offenders with a respect lacking in alternative criminal justice systems; retributivism presumably recognizes that offenders are fellow members of the moral community who can be held responsible for their actions. One version of the respect argument builds on P.F. Strawson’s moral responsibility theory. According to Strawson, we may take either a participant or objective attitude toward other people. The former is the default attitude when interacting with other adults, whereas the latter is fit for children and the mentally disabled or ill, whom we merely try to manage and handle as best we can. The participant attitude also involves holding people responsible when they do wrong. Supposedly, a retributivist criminal justice system functions as a natural continuation of our everyday, participant, and responsibility-holding practices, unlike alternative systems that adopt an objective attitude toward offenders. I argue that this is wrong. The participant attitude requires reciprocity and, usually, some level of equality too. Even an idealized retributivist system has little room for this, not to mention the flawed versions of this system we see in reality.